2021
DOI: 10.1007/s00125-021-05499-z
|View full text |Cite
|
Sign up to set email alerts
|

Retinal arteriolar tortuosity and fractal dimension are associated with long-term cardiovascular outcomes in people with type 2 diabetes

Abstract: Aims/hypothesis Our aim was to determine whether quantitative retinal traits in people with type 2 diabetes are independently associated with incident major cardiovascular events including CHD and stroke. Methods A total of 1066 men and women with type 2 diabetes, aged 65–74 years, were followed up over 8 years in the population-based Edinburgh Type 2 Diabetes Study. Using retinal photographs taken at baseline and specialist software, a number of quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
(43 reference statements)
3
13
0
Order By: Relevance
“…For retinal fractal dimension characteristics, we found a negative association of MAangle, MAasymmetry, and MVasymmetry with CHD. Similar associations have been found with cerebrovascular events and stroke previously [ 74 ]. We have also found larger occlusion and more exudates in the CHD group than the control group in this study, consistent with previous studies [ 75 , 76 , 77 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For retinal fractal dimension characteristics, we found a negative association of MAangle, MAasymmetry, and MVasymmetry with CHD. Similar associations have been found with cerebrovascular events and stroke previously [ 74 ]. We have also found larger occlusion and more exudates in the CHD group than the control group in this study, consistent with previous studies [ 75 , 76 , 77 ].…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have reported positive associations between retinal vessel tortuosity and cyanotic CHD, intracranial artery atherosclerosis, diabetes, and cerebrovascular events. However, one research study reported a negative association with ischemic heart disease death [ 68 , 71 , 72 , 73 , 74 ]. Our study result demonstrated a positive association between retinal vessel tortuosity and CHD.…”
Section: Discussionmentioning
confidence: 99%
“…3 Subtle alterations of the retinal status, as arterial tortuosity and fractal dimension, can even predict such events in the absence of diabetic retinopathy. 4 Due to the lower effective of our population, our analysis does not question the relevance of Khunti's findings: we agree that CKD and conventional risk factors can be considered as interesting predictors of cardiovascular events in type 2 diabetes. A problem may, however, rise if the categorization to high cardiovascular risk leads to prescribe new antidiabetic drugs like GLP-1 receptor agonists, as suggested by Khunti.…”
Section: Diabetic Retinopathy Is Also An Important Marker Of Cardiova...supporting
confidence: 64%
“…FAZ area is a metric that correlates to DR stage, predicts risk of progression to a more severe DR stage, and has been very recently associated with long-term cardiovascular outcomes in people with T2D [ 16 ]. A recent meta-analysis by Zhang et al (2021) [ 17 ] compiled and analyzed 2241 diabetic eyes and showed that FAZ area increased with worsening DR and in DR-free patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%